The Dynamic Continental Margin Between the Mid-Atlantic-Ridge System (Mohns Ridge, Knipovich Ridge) and the Bear Island Region - Schweitzer, J.; Mjelde, R.; Krüger, F.; Guterch, A.; Schmidt-Aursch, Mechita C.; Grad, M.; Faleide, J. I.; IPY Project Consortium (2010)
The aims of this study are the investigation of the Earth's structure and dynamics at the continental margin between the mid-Atlantic-ridge system (Mohns and Knipovich Ridges) and the Bear Island (Bjørnøya) region from its top sedimentary cover to its imprint in the upper mantle. In this region the margin includes an extremely thick sedimentary wedge and steep slopes, with at least one major paleo-fracture zone cutting through the wedge. Recent studies in this area indicate very low seismic velocities in the lithosphere and the stress field undergoes an extensional-compressional transition. It is therefore of particular interest to understand the structural architecture, the stress and the dynamics of the whole region because of its natural hazard exposure and the processes involved in the formation of the margin and the opening of the North Atlantic.To obtain such information, detailed monitoring and analysis of the seismicity between the margin and the mid-Atlantic ridges are necessary. To achieve this, deep seismic sounding data, as well as records from temporary broadband installations, supplementary to data from existing seismic stations in the region were collected. In autumn 2007, we began withseismological field experiments along the continental margin of the Barents Sea near Bear Island (Bjørnøya) and the Mohns and Knipovich Ridges. The field experiments comprise the installation and parallel operation of several seismic instruments during 2007-2008 such as 12 broadband Ocean Bottom Seismometers (OBSs), two new broadband seismometers, a small temporary seismic array with 13 sensors and active seismicrefraction/reflection experiments along two profiles crossing the region and recorded with additional short period OBSs and land stations.First results of the joint data analysis with respect to seismicity and crustal structure in the region of interest will be presented.